The innovations in China's primary health care reform: Development and characteristics of the community health services in Hangzhou. Issue 3 (1st September 2015) - Lin, Feng; Sun, Qihong; Peng, Zhangping; Cai, Jun; Geanacopoulos, Philip; Li, Lin; Zhao, Yun; Zhang, Xin; Chen, Xiaoxiao
Abstract : Objective: This study focuses on Hangzhou, a Chinese city with a population of nine million urban and rural residents, to examine the successful development and innovation experience of its primary health care service system during the new health reform in China since 2009 and then disseminate the findings through international third parties. Methods: Measures such as data analysis, study of documents and regulations, fieldwork, and expert discussions were used to systematically investigate primary health care in Hangzhou. The findings will have a profound practical impact on the health reform for nine million rural and urban residents throughout Hangzhou's municipal boroughs. Results: Community health services in Hangzhou are characterized as follows: They are government led; they are guaranteed with enough financing, personnel, facilities, and regulation; supported by the unified information platform; general practitioners have been assigned the key role of health 'gatekeepers'; they provide primary care combined with basic public health services; there are integrated urban and rural health services and insurance coverage; and there is health care–pension–nursing integration and general practitioner – contracted 'smart' services. Preliminary data collection and analysis indicate that the basic health status of Hangzhou residents is superior to that of residents of China as a whole, and some health indicators in Hangzhou are comparable to those in Western developed countries. Conclusion: It is reasonable to believe that the primary health care level in China, including Hangzhou, will be further developed and promoted with indexed performance evaluations and more effective implementation of additional measures.